On the use of belief revision to merge description logic terminologies - Moguillansky, Martín O. (2006)
Distributed ontologies expressed as description logics may define repeated information. To reason about concepts that these ontologies express, a possible option is to generate unique concept definitions in a different terminology or TBox. The creation of a new terminology from different ontologies need to be consistent, and expressed with non-monotonic logics to be further updated with new distributed ontologies. The model AGM of theory change seems to be an interesting framework to be studied in conjunction with description logics and generate a new non-monotonic description logics model.